Creación de un programa de iniciación para garantizar el proceso de rendimiento en los nadadores de la “escuela de natación de la federación deportiva de Chimborazo” en el año 2011. - Siza Pillajo, Lilian Patricia (2010)
Creating an induction program to ensure process performance swimmers "swimming school of the Sports Federation of Chimborazo" in 2011. This research was conducted in the pool of Chimborazo Sports Federation for the purpose of creating an induction program that ensures sporting performance of the swimmers children, this research was conducted in order to help foster solutions to a problem that worsens each Again the swimmers in the province negative outcomes nationally and internationally, verify that the creation of an induction program guarantee the process performance swimmers Swim School Sport Federation Chimborazo in 2011 . Athletic performance is a chronological process of teaching and learning based on skills acquisition skills, skills to function effectively in sports and is the result you get an athlete during a competition that reflects statistical parameters such as size and brand, not necessarily ends with success. This work is a descriptive transversal field, giving an analysis of the various tests with rating parameters for application to the study, was performed with 10 athletes Swim School Sports Federation of Chimborazo, who contributed to this Research will play in the best way.